PENDEKATAN FENOMENOLOGI DALAM PENYUSUNAN PORTOFOLIO MAHASISWA DI ERA AI - Ramandika Arya Wibowo; M. Farhan Maheswara; Davin Rachmada Adhka; Yusuf Amrozi (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
The integration of Artificial Intelligence (AI) has significantly transformed student portfolio creation in higher education. This presents an urgent problem regarding academic authenticity, yet the subjective student experience remains largely unexplored. Therefore, this study aims to understand the lived experience of students interacting with AI during this process. Employing a qualitative phenomenological approach, data were collected through in-depth interviews with three university students. The results reveal a paradoxical experience: AI is perceived as both a practical accelerator and a source of anxiety concerning originality and the devaluation of personal skills. This experience unfolds through a systematic flow, beginning with functional adoption, leading to internal conflict, and resulting in a continuous negotiation of meaning. Interpreted through the Technology Acceptance Model (TAM) and Technology Dependency Theory (TDT), these findings conclude that a pedagogical shift from mere restriction towards fostering critical AI literacy is necessary to uphold academic integrity.